A survey of physiotherapy practice (2018) in the United Kingdom for patients with greater trochanteric pain syndrome. (April 2019) - Stephens, Gareth; O'Neill, Seth; French, Helen P.; Fearon, Angela; Grimaldi, Alison; O'Connor, Louise; Woodley, Stephanie; Littlewood, Chris
Abstract: Purpose: Greater Trochanteric Pain syndrome (GTPS) is a debilitating condition causing lateral hip pain. It affects up to 23.5% of women and 8% of men between 50 and 75 years old. Sufferers report comparable quality of life and functional performance to patients with end stage osteoarthritis of the hip. Understanding of optimal management strategies for GTPS remains limited. Hence, the purpose of this cross-sectional survey was to describe current UK physiotherapy practice so as to understand current practice and inform the systematic development of a physiotherapy intervention. Methods: An online survey was developed and distributed via Twitter, the interactive Chartered Society of Physiotherapy website, Musculoskeletal Association of Chartered Physiotherapists and the professional networks of the authors via email. Responses were collected over a four-week period, this was finalised in April 2018. Results: A total of 409 surveys were submitted; 382 were eligible for use. Nearly all physiotherapists were either somewhat, or very confident diagnosing (372/382; 97.4%) and treating (372/382; 97.4%) patients with GTPS. The management strategies most commonly used were: education on load management (377/381; 98.7%) and self-management strategies (375/381; 98.4%). Strengthening exercises (376/382; 98.4%) were commonly used and targeted to the hip abductors (355/379; 93.7%). Most frequently these exercises were delivered using a combination of home exercise programme (380/380; 100%) and one-to-one exercise sessions (344/377; 91.2%). Conclusion: The data from this large survey highlights that physiotherapists in the UK most commonly use education on load management and self-management strategies, alongside strengthening exercises targeting the hip abductors for patients with GTPS. Highlights: Were confident in their ability to diagnose and treat patients with GTPS. Use a variety of patient reported and clinical examination findings to diagnose GTPS. Most commonly educate patients with GTPS on load and self-management strategies. Most commonly prescribe strengthening exercises, targeted to the hip abductors.